Synthesis and Cytotoxic Activity of Novel Indole Derivatives and Their in silico Screening on Spike Glycoprotein of SARS-CoV-2 - Gobinath, Perumal; Packialakshmi, Ponnusamy; Vijayakumar, Kaliappillai; Abdellattif, Magda H.; Shahbaaz, Mohd; Idhayadhulla, Akbar; Surendrakumar, Radhakrishnan (Frontiers in Molecular Biosciences, 2021)
Abstract This work, investigated the interaction of indole with SARS-CoV-2. Indole is widely used as medical material owing to its astounding biological activities. Indole and its derivatives belong to a significant category of heterocyclic compounds that have been used as a crucial component for several syntheses of medicine. A straightforward one-pot three-component synthesis of indole- coupled with a Mannich base derivatives 1a–1j were synthesized without a catalyst. The products were confirmed by IR, 1H-NMR, ¹³C-NMR, mass spectra, and elemental analysis. The indole derivatives were tested for cytotoxic activity, using three cancer cell lines and normal cell lines Human embryonic kidney cell (HEK293), liver cell (LO2), and lung cell (MRC5) by MTT assay using doxorubicin as the standard drug. The result of cytotoxicity indole compound 1c (HepG2, LC50-0.9μm, MCF-7, LC50- 0.55μm, HeLa, LC50-0.50μm) was found to have high activity compared with other compounds used for the same purpose. The synthesized derivatives have revealed their safety by exhibiting significantly less cytotoxicity against the normal cell line (HEK-293), (LO2), and (MRC5) with IC50 > 100 μg/ml. Besides, we report an in-silico study with spike glycoprotein (SARS-CoV-2-S). The selective molecules of compound 1c exhibited the highest docking score -2.808 (kKcal/mol) compared to other compounds. This research work was successful in synthesis a few compounds with potential as anticancer agents. Furthermore, we have tried to emphasize the anticipated role of indole scaffolds in designing and discovering the much-awaited anti-SARS CoV-2 therapy by exploring the research article depicting indole moieties as targeting SARS CoV-2 coronavirus.